Democracy and the Epistemic Limits of Markets. Issue 1 (2nd January 2019) - Elliott, Kevin J.
ABSTRACT: A recent line of argument insists that replacing democracy with markets would improve social decision making due to markets' superior use of knowledge. These arguments are flawed by unrealistic assumptions, unfair comparisons, and a neglect of the epistemic limits of markets. In reality, the epistemic advantages of markets over democracy are circumscribed and often illusory. A recognition of markets' epistemic limits can, however, provide guidance for designing institutions in ways that capture the advantages of both.